Monitoring Human Neutrophil Differentiation by Digital Holographic Microscopy - do R. B. F. Lima, Maria Augusta; Cojoc, Dan (Frontiers in Physics, 2021)
The paper reports on the usefulness of digital holographic microscopy (DHM) for the assessment of human neutrophils differentiation from myeloid cells. The changes of nucleus morphology, in relation to the whole cell morphology, have been examined during the process of granulocytic differentiation into mature neutrophils. It is shown that nucleus circularity and volume, and the ratios between the nucleus and the cell projected area and volume provide a reliable set of parameters to characterize the maturation process. As control, cell differentiation has been monitored in parallel using standard nucleus staining and fluorescence imaging. From this research it emerges that DHM can be used as a valid free-label solution, alternatively to the standard staining technology.